The sweetness of freedom : stories of immigrants - Ostrander, Stephen Garr (Book collections on Project MUSE., 2010)
The Sweetness of Freedom presents an eclectic grouping of late nineteenth- and twentieth-century immigrants' narratives and the personal artifacts, historical documents, and photographs these travelers brought on their journeys to Michigan. Most of the oral histories in this volume are based on interviews conducted with the immigrants themselves. Some of the immigrants presented here hoped to gain better education and jobs. Others - refugees - fled their homelands because of war, poverty, repression, religious persecution, or ethnic discrimination. All dreamt of fre.